Strategi Dakwah Pesantren Mawaridusslam Kec. Batang Kuis, Kab. Deli Serdang Dalam Membina Akhlak Santri - Ricky Andre Ricky Harahap; Ahmad Thamrin Sikumbang (Hikmah, 2025)
Preaching strategy is a method used to uphold the teachings of Islam, particularly in the environment of Islamic Boarding Schools. This paper aims to understand and explore the preaching strategies that support the development of students' moral character at the Mawaridussalam Islamic Boarding School. The research model applied in this study is field research. The author collected primary data through observation and interviews, complemented by the analysis of relevant journal articles, literature reviews, and reports from related institutions. The findings of the study reveal that preaching strategies play a vital role in the process of moral development among students and serve as key indicators in shaping commendable moral behavior. At Mawaridussalam Islamic Boarding School, two primary preaching methods are implemented: the uswah hasanah (exemplary model) method and the mau’izhah hasanah (wise advice) method. These strategies are embedded in the daily routines and interactions between teachers and students, creating a conducive environment for character education. The study highlights that the use of these approaches not only strengthens the moral foundation of the students but also fosters a culture of mutual respect, discipline, and spiritual awareness. The conclusion of the research underlines the importance of effectiveness and consistency in applying preaching strategies as a means of moral development. It suggests that the success of Islamic Boarding Schools in fostering students' morals is significantly influenced by how well these preaching strategies are planned and executed in daily practice.